Chế tạo vật liệu compozit sinh học trên nền nhựa polyeste không no gia cường bằng sợi nứa có xử lý bổ sung plasma lạnh - Phương Hòa, Tạ Thị; Diệu, Trần Vĩnh; Yến Oanh, Đoàn Thị; Phúc, Mạc Văn (Vietnam Journal of Chemistry, 2014)
After extracting by mechanical (by hand) and machine methods, Neohouzeaua fiber was treated by air plasma at atmospheric pressure with conditions of power 100W, frequency of 17 kHz and different treatment times (from 1 min to 7 min). SE M analyses showed that the fiber surface become rougher after plasma treatment because of the effect of plasma bombardment and etching. The testing on tensile strength and the interfacial shear strength (IFSS) showed that at the optimal treatment time of 4 minutes: the tensile strength of neohouzeaua fiber increased 15.5 percent after air plasma treatment and treated fiber have cleaner surface. IFSS of the treated fiber at 4 minutes increased 51.7% compared with untreated fiber. Unsaturated polyester (USP) resin composites reinforced by neohouzeaua fiber submitted to air plasma treatment and untreated and USP composites reinforced by hybrid neohouzeaua/glass fiber mat were fabricated using a vacuum infusion process (VIP). Mechanical test, SEM and water absorption measurements of the composites have been investigated. These results reveal that atmospheric pressure air plasma treatment is an effective method to improve not only the performance of neohouzeaua fiber but also of UPS-neohouzeaua composites. With hybrid composites with ply-by-ply structure and the content ratio of neohouzeaua/glass of 40/60 (by weight) the received materials has optimal properties, such as tensile, flexural and impact strengths improve 38.9%, 15.5% and 217.5% compare to PC-Neohouzeaua mat, respectively.